SYNTHESIS AND EVALUATION OF ANTIMICROBIAL ACTIVITY OF PYRIMIDINE DERIVATIVES - BHAGCHAND JAT; SWAPNA SANTRA; PRASANTA KUMAR SANTRA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Synthesis, characterization, and evaluation of antimicrobial activity of novel pyrimidine derivatives containing O, N, and S in the ring. Methods: Pyrimidine derivatives were prepared in three steps. In the first step, chalcones containing -NO2 functional group were synthesized using Claisen-Schmidt condensation of aromatic aldehydes with 2-acetyl pyridine/3-acetylpyridine in methanol in the presence of aqueous NaOH. In the second step, -NO2 group was reduced to -NH2 group. Resulting compounds containing NH2 functional group were reacted with different dichlorothienopyrimidines and dichlorofuropyrimidines in the presence of N,N-diisopropylethylamine to obtain pyrimidine derivatives.Antibacterial and antifungal activity of pyrimidine derivatives were studied in vitro. Results: Pyrimidine derivatives were synthesized and purified using flash column chromatography. Purity of synthesized pyrimidines was determined by high-performance liquid chromatography. Pyrimidines were characterized by elemental analysis, infrared, nuclear magnetic resonance, and mass spectral analysis. Analytical data of synthesized pyrimidines supported the proposed structures. Significant antibacterial and antifungal activity were observed in the synthesized pyrimidine derivatives. Conclusion: Antibacterial and antifungal activity of the newly synthesized pyrimidine derivatives will definitely inspire future researchers for the preparation of new analogs.